Awersja do nierówności w społeczeństwie polskim - Ulman, Paweł (Inequality Aversion in the Polish Society, 2008)
The aim of the paper is to investigate the inequality aversion in the Polish society. The measurement aversion was made with the use of the Arrow-Pratt function that was based on the utility function. The deductive pattern of thought modus to liens (employed to estimate welfare distribution) was used in order to determine the form of utility function and to estimate its parameters. This approach allowed to assess the level of the inequality aversion in different sections of Polish society in 2005. The statistical data were taken from re sample surveys of households budgets carried out by the CSO in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 165-172